Pendampingan Pembinaan Bolavoli di Kecamatan Teluk Pakedai Kabupaten Kubu Raya - Muhammad Suhairi; Zainal Arifin; Rajidin Rajidin; Syaparudin Syaparudin4, (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community service activity aims to carry out one of the Tridharma of Higher Education, and assist the community in fostering and empowering the potential of Village youth in volleyball sports activities in Teluk Pakedai District. The main problem faced by partners is, in carrying out volleyball activities they do not yet have a coach whose competence is in accordance with volleyball coaching knowledge. do not yet have the ability to compile a good volleyball training program. Knowledge of volleyball game rules is still not good. As well as the lack of existing training facilities to support a good training process, and its supporting facilities. The outcome of this activity is that the trainer has been able to make a good and correct training program in accordance with the principles of coaching science. Availability of standard volleyball training facilities in accordance with the provisions. More and more teenagers are involved in sports activities. The method used to achieve the objectives of this activity are 1). Focus Group discussions; 2). Coaching clinic preparation of training and refereeing programs for volleyball coaches; 3) provision of football and volleyball training tools; 4). Assistance in training and volleyball.